Identifikasi Salah Satu Bentuk Sel Epidermis Pada Beberapa Daun Sub Kelas Asteridae - sri rezeki (Jurnal Biologi dan Pembelajarannya (JB&P), 2023)
The epidermis is the layer of cells on the outside and covers the surface ofleaves, flowers, fruits, seeds, stems and roots. The function of the epidermis isto protect the internal organs of the plant. Based on its function, the epidermiscan develop and undergo modifications like stomata and trichomes. Thisresearch was conducted with the aim of identifying one of the epidermalderivatives in plants from the Asteridae subclass. In this study, the method usedto observe epidermal cells was the Halsil descriptive method obtained based onresearch the form of the epidermis on some leaves of the Asteridae subclass,including the frangipani plant (Plumeria) which has stomata of the parasitictype. Furthermore, eggplant (Solanum melongena) has non-glandular typetrichomes. After that, the cayenne pepper (Capsicum sp) had anisocytic type ofstomata. Then the tomato plant (Lypersicum esculentum) has anomocytic typeof stomata. In addition to the derived form of the epidermis on the leaves, thereare stomata, trichomes, bulforms, lithocyte cells and myrosin. Furthermore, inthe stem there are silica cells and cork cells. Then at the root there are roothairs and velamen. Derivatives of the epidermis, Stomata, Trichomes.